POLICY REFOCUSING REGIONAL EXPENDITURE BUDGETS IN HANDLING COVID-19 IN MAJALENGKA DISTRICT - Milawati, Milawati; Sarofah, Riska (Fakultas Politik Pemerintahan, 2023)
This research discusses the policy of refocusing regional budgets in dealing with the COVID-19 pandemic in the Majalengka Regional Government. This issue is important to discuss because it is related to the Covid-19 Pandemic which must be addressed immediately, according to Presidential Instruction No. 4 of 2020 regarding Budget Refocusing Policies, Budget Reallocations, and Procurement of Goods and Services to Accelerate the Handling of COVID-19. The purpose of writing this article is to explain how the Regional Budget Refocusing policy is related and what impact this policy has. This study used a qualitative method with literature study, namely by collecting information relevant to the problem being studied, such as notes, literature, as well as various reports related to the problem, and verifying to make a conclusion. The results of this study found that on the one hand, the implementation of budget refocusing was considered appropriate in accelerating the handling of COVID-19, on the other hand, the budget refocusing policy was not effective given that there were still many local governments that were constrained and ineffective in refocusing the regional budget.